2012
DOI: 10.1016/j.jaci.2012.06.025
|View full text |Cite
|
Sign up to set email alerts
|

Periostin is a systemic biomarker of eosinophilic airway inflammation in asthmatic patients

Abstract: Background Eosinophilic airway inflammation is heterogeneous in asthmatic patients. We recently described a distinct subtype of asthma defined by the expression of genes inducible by TH2 cytokines in bronchial epithelium. This gene signature, which includes periostin, is present in approximately half of asthmatic patients and correlates with eosinophilic airway inflammation. However, identification of this subtype depends on invasive airway sampling, and hence noninvasive biomarkers of this phenotype are desir… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

21
398
8
7

Year Published

2013
2013
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 545 publications
(434 citation statements)
references
References 66 publications
21
398
8
7
Order By: Relevance
“…This fits well with the observed correlation between periostin and specific IgE in sputum [45]. After this initial report, several investigators confirmed the association between periostin and sputum eosinophils, even proposed serum periostin as a biomarker for airway eosinophilia [42]. However, subsequent studies showed that the strength of the correlation between periostin and sputum eosinophilia, although significant, was relatively weak, and that neither serum nor sputum periostin was suitable for use as a surrogate marker of airway eosinophilia [43].…”
Section: Periostinsupporting
confidence: 79%
See 3 more Smart Citations
“…This fits well with the observed correlation between periostin and specific IgE in sputum [45]. After this initial report, several investigators confirmed the association between periostin and sputum eosinophils, even proposed serum periostin as a biomarker for airway eosinophilia [42]. However, subsequent studies showed that the strength of the correlation between periostin and sputum eosinophilia, although significant, was relatively weak, and that neither serum nor sputum periostin was suitable for use as a surrogate marker of airway eosinophilia [43].…”
Section: Periostinsupporting
confidence: 79%
“…Several reports have shown significant correlations between periostin in serum and eosinophils in sputum [42,43]. Woodruff et al were the first to show upregulated periostin gene expression in bronchoalveolar lavage from patients with asthma as compared to normal control subjects, which was associated with increased concentrations of IL-4, IL-5, and IL-13 [44].…”
Section: Periostinmentioning
confidence: 99%
See 2 more Smart Citations
“…In a post-hoc analysis, this antibody improved prebronchodilator FEV1 in the group with evidence for Th2 inflammation as measured by elevated serum periostin levels, a proposed surrogate marker of Th2 activity or FeNO [59,223]. Another anti-IL-13 antibody, tralokinumab, did not improve symptoms but resulted in a non-significant increase in FEV1 when compared to placebo in all comers.…”
Section: Remarksmentioning
confidence: 89%